Posterior pericardiotomy in cardiac surgery: systematic review and meta-analysis: - Ali-Hassan-Sayegh, Sadegh; Mirhosseini, Seyed Jalil; Liakopoulos, Oliver Johannes; Sabashnikov, Anton; Dehghan, Hamid Reza; Sedaghat-Hamedani, Farbod; Kayvanpour, Elham; Ghaffari Mehjerdi, Naser; Vahabzadeh, Vahid; Aghabagheri, Mahdi; Mozayan, Mohammad Reza; Popov, Aron-Frederik (Asian cardiovascular & thoracic annals, 2015)
This systematic review with meta-analysis sought to determine the impact of posterior pericardiotomy on incidences of atrial fibrillation and supraventricular a...